PENGGUNAAN MEDIA GAMBAR LUAS DAERAH UNTUK MENINGKATKAN KEMAMPUAN MENJUMLAH PECAHAN PESERTA DIDIK KELAS IV SDN BANJARSUGIHAN 1/116 SURABAYA - Pratiwi Santoso, Yulia; Vicky Dwi Wicaksono; Titik Indrayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mathematics learning is often found in everyday life, such as fractions. Fractions are part of a whole. There are various kinds of fractions, namely simple fractions and non-simple fractions. Non-simple fractions are fractions whose numerator can still be simplified further by using area-wide image media to improve the ability to add fractions of class IV students at SDN Banjarsugihan 1/116 Surabaya. The purpose of this research is to determine the use of area-wide image media to increase students' ability to add fractions. Class IV students at SDN Banjarsugihan 1/116 Surabaya. The form of this research is Classroom Action Research using the Cycle model. Each cycle consists of 4 stages, namely: planning, implementing actions, observing and reflecting. As subjects were Class IV students at SDN Banjarsugihan 1/116 Surabaya, totaling 26 students. Subjects were taken using a quantitative descriptive approach. Data collection techniques use interviews, observation and written tests. The results from cycle I experienced an increase in value of ≥ 0.4 in the moderate improvement category, while in cycle II a value of ≥ 0.7 was obtained in the high improvement category. Based on this research, it can be concluded as follows: The use of area-wide image media can increase the ability to add fractions to class IV students at SDN Banjarsugihan 1/116 Surabaya.